Daptomycin-based aminoglycoside-sparing therapy for streptococcal endocarditis: a retrospective multicenter study. (21st September 2021) - Pallotto, Carlo; Sbrana, Francesco; Ripoli, Andrea; Lupia, Tommaso; Corcione, Silvia; Paciosi, Francesco; Francisci, Daniela; Pasticci, Maria Bruna; Sozio, Emanuela; Bertolino, Giacomo; Carannante, Novella; Rescigno, Carolina; et al.
Abstract : Streptococci still represent common etiologic agents of infective endocarditis (IE). Although renal failure is frequently reported as an aminoglycoside-associated adverse event, last international guidelines recommend a beta-lactam/gentamicin combination therapy. We retrospectively evaluated the use of daptomycin-based aminoglycoside-sparing combination therapy for the treatment of streptococcal IE in seven referral hospitals in Italy. Retrospective, multicenter, observational study. All patients with streptococcal IE admitted from 2016 to 2018 were enrolled. Mortality and incidence of acute kidney injury (AKI) were compared between Group A (standard of care, SoC) and Group B (daptomycin-based aminoglycoside-sparing combination therapy). Fifty-four patients were enrolled, 33 in Group A and 21 in Group B. Mortality was 2/33 (6%) in Group A and 0 in Group B ( p  = 0.681); AKI incidence was 8/33 (24%) in Group A and 0 in Group B ( p  = 0.04). Daptomycin-based aminoglycoside-sparing combination therapy appears to be promising for the treatment of streptococcal endocarditis because of similar efficacy compared with SoC and significantly reduced incidence of AKI.